Anti- Fatigue Rubber Mat for Industrial Workplace: Load Pressure Analysis at Different Type of Mats - Mustafa Kamal, Mazlina; Kamarularifin, H; Che Mat, Che Muhd Firdaus (Journal of Advanced Research in Applied Mechanics, 2020)
The material from natural rubber/recycle rubber blends produced will be used as antifatigue mat for prolonged standing worker in the industrial workplace applications. Many industrial workplaces dealing with standing position worker especially in processes job. The employer believes that performing jobs in standing position will give more degree of freedom especially operating large machine which will increase the productivity. The commercialized anti-fatigue rubber mat was used to compare the load and pressure analysis between conventional and formulated anti-fatigue mats. The study focused on the contact area, force in % body weight, contact pressure, and force applied on to the mats. The result showed that the conventional mat gave highest pressure recorded at 0.15MPa. The high pressure contact will increase the fatigue condition thus increased the tiredness feeling. The commercial anti- fatigue mat gave lowest value (44.54%) of normalized force meaning that almost 55.5% bodyweight was absorbed by mat followed by formulated mat and conventional mat.